Transgenic Mice Reveal Unexpected Diversity of On-Off Direction-Selective Retinal Ganglion Cell Subtypes and Brain Structures Involved in Motion Processing - Rivlin-Etzion, Michal (Society for Neuroscience, 2011)
On-Off direction-selective retinal ganglion cells (DSGCs) encode the axis of visual motion. They respond strongly to an object moving in a preferred direction and weakly to an object moving in the opposite, “null,” direction. Historically, On-Off DSGCs were classified into four subtypes according to their directional preference (anterior, posterior, superior, or inferior). Here, we compare two genetically identified populations of On-Off DSGCs: dopamine receptor 4 (DRD4)-DSGCs and thyrotropin-releasing hormone receptor (TRHR)-DSGCs. We find that although both populations are tuned for posterior motion, they can be distinguished by a variety of physiological and anatomical criteria. First, the directional tuning of TRHR-DSGCs is broader than that of DRD4-DSGCs. Second, whereas both populations project similarly to the dorsal lateral geniculate nucleus, they project differently to the ventral lateral geniculate nucleus and the superior colliculus. Moreover, TRHR-DSGCs, but not DRD4-DSGCs, also project to the zona incerta, a thalamic area not previously known to receive direction-tuned visual information. Our findings reveal unexpected diversity among mouse On-Off DSGC subtypes that uniquely process and convey image motion to the brain.